Nanovector-mediated exogenous delivery of dsRNA induces silencing of target genes in very young tomato flower buds. Issue 21 (22nd September 2022) - Molesini, B.; Pennisi, F.; Cressoni, C.; Vitulo, N.; Dusi, V.; Speghini, A.; Pandolfini, T.
Abstract : We propose a method to deliver nanoparticle-coupled dsRNA to tomato flower buds to silence endogenous genes. Abstract : RNA interference (RNAi) is a post-translational regulatory mechanism that controls gene expression in plants. This process can be artificially induced by double-stranded RNA (dsRNA) molecules with sequence homology to target mRNAs. Exogenously applied dsRNA on leaves has been shown to silence virulence genes of fungi and viruses, conferring protection to plants. Coupling dsRNA to nanoparticles has been demonstrated to prolong the silencing effect. The ability of exogenous dsRNA to silence endogenous genes in plants is currently under debate, mainly due to the difficulty in delivering dsRNA into plant tissues and organs. Our study aims to develop a method based on the exogenous application of dsRNA on tomato flowers for silencing endogenous genes controlling ovary growth. Two methods of dsRNA delivery into tomato flower buds ( i.e., pedicel soaking and injection) were compared to test their efficacy in silencing the tomato Aux/IAA9 ( SlIAA9 ) gene, which encodes for a known repressor of ovary growth. We examined the silencing effect of dsRNA alone and coupled to layered double hydroxide (LDHs) nanoparticles. We found that injection into the pedicel led to the silencing of SlIAA9 and the efficacy of the method was confirmed by choosing a different ovary growth repressor gene ( SlAGAMOUS-like 6 ; SlAGL6 ). The coupling of dsRNA to LDHs increased the silencing effect in the case of SlIAA9 . Silencing of the two repressors caused an increase in ovary size only when flower buds were treated with dsRNA coupled to LDHs. RNA-Seq of small RNAs showed that induction of RNAi was caused by the processing of injected dsRNA. In this work, we demonstrate for the first time that exogenous dsRNA coupled to LDHs can induce post-transcriptional gene silencing in the young tomato ovary by injection into the flower pedicel. This method represents a silencing tool for the study of the molecular changes occurring during the early stages of ovary/fruit growth as a consequence of downregulation of target genes, without the need to produce transgenic plants stably expressing RNAi constructs.